Productive behavior and phenotypic stability of Hordeum vulgare L. in Colombia - Campuzano-Duque, Luis Fernando; Avendaño-Avendaño, Diego Fernando; Luque-Sanabria, Nadia Yurani (Agronomía Mesoamericana, 2021)
Introduction. The incorporation of 40 thousand hectares of barley (Hordeum vulgare L.) for the beer industry in Colombia, with a projected production of 80 thousand t yr-1 in the period 2016 to 2026, will allow to reduce imports by 60 %. However, meeting this goal requires high-yielding, high-quality barley varieties. Objective. To identify a barley variety with stable grain yield and higher than 2.6 t ha-1 associated with tolerance to tipping, lower severity to yellow rust on the leaf and ear, and physical quality of the grain for the brewing industry. Materials and methods. Between 2016 and 2017, an agronomic evaluation trial was carried out in the Colombian Andean region, in a randomized complete block design, with eight two-row barley varieties introduced to Colombia. The physiological maturity, tipping, severity to Puccinia striiformis f. sp hordei in the leaf and ear, grain yield, and hectoliter weight were determined. Results. The Madi and S5 varieties with grain yields of 2.89 and 2.61 t ha-1, respectively, were 24 and 16 % higher than Metcalfe and 19 and 11 % higher than Maltera 5. Both varieties showed broad phenotypic stability, tolerance to tipping, lower severity of leaf and ear rust, and a hectoliter weight suitable for the brewing industry. Conclusion. The production characteristics, phenotypic stability, and physical quality of the grain of Madi and S5 varieties make them commercial candidates for the brewing industry and for recommendation in the Cundiboyacense highlands of Colombia, after validation with a semi-commercial trial.